2018
DOI: 10.1186/s40169-018-0192-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles as circulating cancer biomarkers: opportunities and challenges

Abstract: Extracellular vesicles (EVs) are small, lipid-bound particles containing nucleic acid and protein cargo which are excreted from cells under a variety of normal and pathological conditions. EVs have garnered substantial research interest in recent years, due to their potential utility as circulating biomarkers for a variety of diseases, including numerous types of cancer. The following review will discuss the current understanding of the form and function of EVs, their specific role in cancer pathogenesis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
163
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(165 citation statements)
references
References 117 publications
0
163
0
2
Order By: Relevance
“…Given that proteins are critical bioactive constituents of EV cargo, proteomic approaches are appealing to compare molecular profiles of different EV types and provide invaluable insights into the nature of EV heterogeneity. Moreover, EV cargo has been demonstrated to include cancer‐specific proteins and EV potential to serve as a source of circulating biomarkers has been under vigorous investigation. Therefore, defining discrete EV populations enriched in tumor‐derived proteins, as well as development of novel technologies that would allow EV isolation from clinical samples more efficiently, is of utter importance.…”
Section: Introductionmentioning
confidence: 99%
“…Given that proteins are critical bioactive constituents of EV cargo, proteomic approaches are appealing to compare molecular profiles of different EV types and provide invaluable insights into the nature of EV heterogeneity. Moreover, EV cargo has been demonstrated to include cancer‐specific proteins and EV potential to serve as a source of circulating biomarkers has been under vigorous investigation. Therefore, defining discrete EV populations enriched in tumor‐derived proteins, as well as development of novel technologies that would allow EV isolation from clinical samples more efficiently, is of utter importance.…”
Section: Introductionmentioning
confidence: 99%
“…HOTAIR mediates EMT because of cigarette smoke extracts [172], and similar studies have indicated that MALAT1 is involved in cigarette smoke extractinduced EMT and malignant transformation [172]. Circulating extracellular vesicles (EVs) can transfer biomolecules, including ligands, cytokines, and genetic information, to recipient cells to enact functional changes [173]. EVs can contain relatively stable RNA species, including small noncoding RNAs and lncRNAs [174].…”
Section: Discussionmentioning
confidence: 99%
“…While a majority of EV‐based diagnostics focuses on nucleic acid including mRNA, miRNA, and lncRNA in EVs, identifying EV‐protein biomarkers may enable rapid screening and identification of cancer status. For detailed development on EV diagnostics via nucleic acid analyses, please refer to Lane et al Differing from blood‐based cancer proteomics, proteomics analysis of isolated tumor EVs may significantly reduce noncancer‐specific proteins, thereby increasing S/N ratio for biomarker identification. In fact, an increasing array of EV biomarkers have since been reported for many cancer types (Table ).…”
Section: Evs In Cancer Diagnosticsmentioning
confidence: 99%